Fat Jersey Blues - Repp, John (Book collections on Project MUSE., 2014)
I know I'm holding a good book in my hand when I use the other to call my friends and read poems to them. How generous John Repp is! He zooms in on the moment, but he's always glancing at everything that surrounds it. His funny poems have dark hearts, just as the sad ones are clearly written by someone capable of belly-shaking laughter. They tell wonderful stories, yet they contain chewy little nuggets that are often indifferent and even hostile to story. I've said elsewhere that a poem either writes you a check or sends you a bill, and Fat Jersey Blues writes me checks faster than I can cash them. Oh, and these poems make me do something else that the good ones always do: when I hung up after reading Bob Johnson or The Maltese Falcon or Balcony to a friend, I sat down to write myself. --David Kirby, author of The Biscuit Joint Saturated with the particularity of place, Fat Jersey Blues dramatizes a world at once actual and mythic, joyful and desolate. As American as this book is, Proust comes to mind when reading it, time slowed to the tempo of a wide river sweeping all that is mortal toward its inevitable end. As Repp writes, " ... how can those days & these & all the others I can't fit/into whatever I'm saying here be lived by one person?" Lucky for us, he's made all "those days and these" fit into this marvelous book. --Lynn Emanuel, author of Noose and Hook How rich the trove of personal, musical, and literary knowledge John Repp brings to this return to the New Jersey of his early years. The warm, adult gaze behind even the angers and disappointments in these poems is what I love in them. --Eric Torgersen, author of Heart. Wood John Repp's poems bear the weight of years as they strip away pretensions of all sorts. Who else could write a fully realized poem that so hilariously praises and corrects another poet, "My Wife's Ass (or 'You Annoy Me, Matthew Dickman!')"? Whether sorrowing or comical, Fat Jersey Blues is never predictable. --Lee Upton, author of The Tao of Humiliation These are poems of elegance and intimacy, informed with earned wisdom and great heart. When Blueberry (or 'Another Summer-of-1975 Poem')--one of the best narrative poems anywhere--urges you to Gather with me in the kitchen where the floorboards/ sag & squeak ... accept the invitation. You will return to Fat Jersey Blues often, grateful to be reminded how rare and essential poets of John Repp's caliber are. --Linda Lee Harper, author of Kiss, Kiss